Intangible Culture on Inland Seas, from Hudson Bay to Canadian Heritage - Brown, Jennifer (Ethnologies, 2014)
The author of this article examines the ways in which the Convention for the Safeguarding of Intangible Cultural Heritage considers the protection of aboriginal languages and provides a case study of the challenges of the preservation of the Cree language in Canada. For Indigenous people, in Canada as elsewhere, questions arise about who speaks for whom; many of their constituents may not identify with the major political organizations that represent their interests to governments and are recognized by government agencies; and other structural and logistical barriers also arise. The paper takes a look at the richness of Aboriginal history around Hudson Bay as held in language and stories, and then discusses the many challenges that a Hudson Bay Cree storyteller, Louis Bird, and his collaborators faced in pursuing an oral history project funded by a Canadian governmental agency with its own parameters and priorities.